The Application of Diversion to Perpetrators of Criminal Acts Committed by Minors Based on Article 1 Number 7 of Law Number 11 of 2012 Concerning the Juvenile Criminal Justice System - Novelina Mutiara Sariati Hutapea; Jenriswandi Damanik; Desy Kartika Caronina Sitepu; Masdin Saragih (International Journal Labs, 2023)
The role of law enforcers is at the forefront of the legal world in Indonesia at this time the number of cases and resolutions of legal problems that are applied by prioritizing a sense of justice not only prioritizing legal certainty, legal protection for children can be done as an effort to protect the law against various freedoms and human rights of children. This protection of children also includes interests related to child welfare. The protection of children in conflict with the law is a shared responsibility of law enforcement officials. One form of restorative justice is dialogue between Indonesian people, better known as musyawarah for consensus. So that diversion, especially through restorative justice, becomes a reference for very important considerations in solving legal cases concerning children as perpetrators of crimes.